2000
DOI: 10.1016/s0006-3495(00)76854-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conditions Required for X-Ray Diffraction Experiments with Protein Microcrystals

Abstract: The x-ray exposure at which significant radiation damage occurs has been quantified for frozen crystals of bacteriorhodopsin. The maximum exposure to approximately 11-keV x-rays that can be tolerated for high-resolution diffraction experiments is found to be approximately 10(10) photons/microm(2), very close to the value predicted from limits that were measured earlier for electron diffraction exposures. Sample heating, which would further reduce the x-ray exposure that could be tolerated, is not expected to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…The ®rst approach emphasizes the study of diffraction data in reciprocal space; the second emphasizes structural damage in real space. Our study (Teng & Moffat, 2000) and that of Glaeser et al (2000) clearly belong to the ®rst approach; those of Burmeister (2000), and Weik et al (2000) belong mostly to the second. In reciprocal space, the reduction in diffraction quality caused by X-ray radiation damage is evident in the decay of diffraction intensities and in the increase of unit-cell volume, overall B-factor and merged R-factor.…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…The ®rst approach emphasizes the study of diffraction data in reciprocal space; the second emphasizes structural damage in real space. Our study (Teng & Moffat, 2000) and that of Glaeser et al (2000) clearly belong to the ®rst approach; those of Burmeister (2000), and Weik et al (2000) belong mostly to the second. In reciprocal space, the reduction in diffraction quality caused by X-ray radiation damage is evident in the decay of diffraction intensities and in the increase of unit-cell volume, overall B-factor and merged R-factor.…”
Section: Introductionmentioning
confidence: 46%
“…In our previous study (Teng & Moffat, 2000), a striking quantitative feature was observed, that the effect of radiation damage on several Table 1 Comparison of the upper limit for X-ray radiation damage and the lifetime of a 100 mm protein crystal (Teng & Moffat, 2000;Glaeser et al, 2000;Burmeister, 2000). parameters characteristic of the diffraction data quality was linearly dependent on the absorbed dose, up to a threshold value of approximately 1 Â 10 7 Gy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) is direct evidence that radiation damage within the diffracting volume can be reduced by reducing the size of the X-ray beam, as proposed by Nave and Hill (18). Several observations of greater than anticipated robustness of very small (<10 μm) crystals (26,27) or of larger crystals probed with very small (<10 μm) beams (3,28,29) have been attributed to photoelectron escape from the illuminated volume and provided indirect evidence of this phenomenon. In our direct measurements, the sample survivability was increased by a factor of three over the range of beam sizes studied with 18.5-keV incident X-rays.…”
Section: Discussionmentioning
confidence: 79%
“…The air paths before and after the sample, up until the X-ray beamstop, or the cryo-gas stream, also contribute significantly to the background scatter. A reduction in air scatter has been demonstrated for microcrystals on improvements to the collimation and by replacing nitrogen with helium in the cold gas stream (Glaeser et al, 2000). Further enhancements have also been gained through close alignment of the apertures and beamstop to within just a few millimetres of the sample position (Madsen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%